Cloning, expression, and bioinformatics analysis of heavy metal resistance-related genes fd-I and fd-II from Acidithiobacillus ferrooxidans. (25th April 2023) - Leng, Feifan; Wu, Yamiao; Hu, Shu; Jing, Yanjun; Ding, Miao; Wei, Qingwei; Zhang, Qingchun; Wang, Yonggang
Abstract: Five heavy metals were introduced into the bacterial heavy metal resistance tests. The results showed that apparent inhibition effects of Cd 2+ and Cu 2+ on the growth of Acidithiobacillus ferrooxidans BYSW1 occurred at high concentrations (>0.04 mol l −1 ). Significant differences ( P < 0.001) were both noticed in the expression of two ferredoxin-encoding genes ( fd-I and fd-II ) related to heavy metal resistance in the presence of Cd 2+ and Cu 2+ . When exposed to 0.06 mol l −1 Cd 2+, the relative expression levels of fd-I and fd-II were about 11 and 13 times as much as those of the control, respectively. Similarly, exposure to 0.04 mol l −1 Cu 2+ caused approximate 8 and 4 times higher than those of the control, respectively. These two genes were cloned and expressed in Escherichia coli, and the structures, functions of two corresponding target proteins, i.e. Ferredoxin-I (Fd-I) and Ferredoxin-II (Fd-II), were predicted. The recombinant cells inserted by fd-I or fd-II were more resistant to Cd 2+ and Cu 2+ compared with wild-type cells. This study was the first investigation regarding the contribution of fd-I and fd-II to enhancing heavy metal resistance of this bioleaching bacterium, and laid a foundation for further elucidation of heavy metal resistance mechanisms caused by Fd.